Community Preparedness Model in Landslide Disaster Risk Reduction in Tugumukti Village, Cisarua Subdistrict, West Bandung District, Indonesia - Ichwan Muis; Khairil Anwar (Asian Social Work Journal, 2018)
This research is aimed to describe handling model toward disaster-prone and vulnerable condition in Tugumukti Village through community preparedness in the effort of Community-based disaster risk reduction. It is an approach to encourage local community in managing disaster risk. This approach is expected to create an independent community and have abilities in managing disaster risk. Preparedness is one important part in reducing disaster risk which demands ability and community participation especially people who live in the disaster-prone area. This research used qualitative action research where the researcher is the research instrument. The action research requires the researcher to do direct practice in the community as the subject being studied. In knowing preparedness in Tugumukti Village based on preparedness framework to disaster developed by LIPI in collaboration with Unesco/ISDR (2006) that is (1) attitude and knowledge system, (2) Policy and Manual, (3) Emergency Planning, (4) Alert System and (5) Resource Mobilization.The research about community preparedness initiated by tested the community preparedness model conducted in three-month practicum, such as (1) ground motion socialization, (2) the installation of banners about landslide (3) 1000 tree planting in landslide area, and (4) drainage channels improvement. Community preparedness model which have been tested in the research is the initial model. The result of the initial model through the interview, FGD and researcher analysis based on preparedness framework toward disaster, then generated that trialing the early models is only just at the stage of the first parameter that is the knowledge and attitudes, while for the other parameters are still said to be less. Based on that, it is necessary to improve the model. In improving the model, participatory action plan formulated by the implementation of the activities through (1) The formation of disaster management community (KMPB), (2) construction and installation evacuation route and meeting point (3) Beras perelek activation, (4) KMPB account making, (5) KMPB post construction, (6) early warning manufacture, (7) disaster equipment procurement, and (8) Training for landslide emergency response simulation.